Value and desirability of water development in East Africa : a re search agenda - Carruthers, I.D
This paper was written as a basis for discussion in the Makerere Eco nomic Research Seminar.
AR/MISR/51/5/1
English
Shelf no. 1.
Keywords: Integrated water development -- Africa, East